2021
DOI: 10.1111/php.13373
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide‐elicited Resistance to Antitumor Photodynamic Therapy via Inhibition of Membrane Free Radical‐mediated Lipid Peroxidation

Abstract: This review focuses on the ability of nitric oxide (NO) to antagonize antitumor photodynamic therapy (PDT). NO’s anti‐PDT effects were recognized relatively recently and require a better mechanistic understanding for developing new strategies to improve PDT efficacy. Many PDT sensitizers (PSs) are amphiphilic and tend to localize in membrane compartments of tumor cells. Unsaturated lipids in these compartments can undergo peroxidative degradation after PS photoactivation. Primary Type I (free radical) vs. Type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 76 publications
(133 reference statements)
0
7
0
Order By: Relevance
“…So far, our understanding of the mechanism of PDT in treating cancer, not only skin cancer, is incomprehensive and incomplete. In our perspective, there are two urgent problems to be addressed that one is "which pathway or molecule is related to the 41 The antitumor effectiveness of PDT can be further improved by finding and removing causes of PDT resistance.…”
Section: Discussionmentioning
confidence: 99%
“…So far, our understanding of the mechanism of PDT in treating cancer, not only skin cancer, is incomprehensive and incomplete. In our perspective, there are two urgent problems to be addressed that one is "which pathway or molecule is related to the 41 The antitumor effectiveness of PDT can be further improved by finding and removing causes of PDT resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that a red laser is able to release NO storage from tissue [48,49]. Lohr et al showed in both purified systems and the myocardium that R/NIR light can decay nitrosyl hemes and release NO, and that this released NO may enhance the cardioprotective effects of nitrite.…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that regarding the NOS activity, scarce studies so far have been reported that explore the possibility of the combination of both the inhibition of NOS, and PDT may potentiate the performance of the photosensitizers (241). Nevertheless, enough evidence has been reported in the literature that these inhibitors might have the potential to be used alone or in combination with other existing therapies such as radiotherapy as well as chemotherapy to explore the possibility of synergistic effects (229,242).…”
Section: Inhibition Of Enzyme Activities Of Relevance For a Synergist...mentioning
confidence: 99%